2017
DOI: 10.1111/famp.12299
|View full text |Cite
|
Sign up to set email alerts
|

What Are They Thinking? A National Study of Stability and Change in Divorce Ideation

Abstract: This study reports on a nationally representative sample of married individuals ages 25-50 (N = 3,000) surveyed twice (1 year apart) to investigate the phenomenon of divorce ideation, or what people are thinking when they are thinking about divorce. Twenty-eight percent of respondents had thought their marriage was in serious trouble in the past but not recently. Another 25% had thoughts about divorce in the last 6 months. Latent Class Analysis revealed three distinct groups among those thinking about divorce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 34 publications
2
24
0
3
Order By: Relevance
“…Recent research on divorce decision‐making may provide a glimpse into why an individual or a couple might postpone help seeking. Hawkins et al (2017) found that individuals who have serious concerns about the health of their marriage tend to vacillate for long periods of time, going back and forth between thinking the marriage can be salvaged and wanting to end the marriage. Presumably, they continue to weigh whether to seek help.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research on divorce decision‐making may provide a glimpse into why an individual or a couple might postpone help seeking. Hawkins et al (2017) found that individuals who have serious concerns about the health of their marriage tend to vacillate for long periods of time, going back and forth between thinking the marriage can be salvaged and wanting to end the marriage. Presumably, they continue to weigh whether to seek help.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on divorce decision-making may provide a glimpse into why an individual or a couple might postpone help seeking. Hawkins et al (2017) found that individuals who have serious…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 14% of data were missing. To estimate missing values, we employed multiple imputation with chained equations (MICE) within the pcAux R package (Lang et al, ) to impute 100 complete data sets (see Hawkins et al, ). With continuous data, MICE has been found to yield similar results as the full information maximum likelihood estimation and the multiple imputation with data augmentation techniques (Azur, Stuart, Frangakis, & Leaf, ; Enders, ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a sophisticated approach to examine these intricacies capable of accounting for various rates of change across time is essential. Recent statistical developments can more fully reflect family and clinical dyadic processes across time, such as: autoregressive models (i.e., inter‐associations across time between multiple variables), latent growth curves (LGC; average rate of change across time; Duncan, Duncan, & Strycker, 2006), and latent class growth analysis (LCGA) or growth mixture models (GMM; multiple paths of change across time; Jung & Wickrama, 2008), latent change score models (Grimm, Ram, & Estabrook, 2017), and latent transition analyses (Hawkins et al., 2017). These techniques vary in the research questions they can address and their focus.…”
Section: Growth Mixture Modeling To Assess Differences In Change Acromentioning
confidence: 99%